2002
DOI: 10.1021/ma011523+
|View full text |Cite
|
Sign up to set email alerts
|

Steady-Shear Rheology of Block Copolymer Melts and Concentrated Solutions:  Disordering Stress in Body-Centered-Cubic Systems

Abstract: We use steady-shear rheology to study the shear-disordering phenomenon in block copolymers in the body-centered-cubic (bcc) mesophase. Polystyrene-polyisoprene and polystyrene-poly-(ethylene-alt-propylene) diblock, triblock, and starblock systems of varying molecular weight and composition were studied in the melt and as concentrated solutions in a selective solvent. The bcc lattice exhibits a low-frequency modulus G bcc 0 which scales with the cube of the lattice spacing and additionally depends only on the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 48 publications
(127 reference statements)
6
69
1
Order By: Relevance
“…This result is in agreement with the works of Sebastian et al (2002a); Sebastian et al (2002b). The slow ordering results from the high temperature the experiment was performed at, which is just slightly below the order-disorder transition temperature T ODT .…”
Section: Isothermal Time Sweep Experimentssupporting
confidence: 92%
See 1 more Smart Citation
“…This result is in agreement with the works of Sebastian et al (2002a); Sebastian et al (2002b). The slow ordering results from the high temperature the experiment was performed at, which is just slightly below the order-disorder transition temperature T ODT .…”
Section: Isothermal Time Sweep Experimentssupporting
confidence: 92%
“…Their study revealed that the steady-state viscosity strongly decreases above a critical shear stress. Furthermore the critical stress is a function of the lattice spacing and the temperature in relation to T ODT (Sebastian et al (2002a).) The phase behavior of various PS-b-PI diblock copolymers was 3 investigated by Förster et al (1994) using transmission electron microscopy (TEM), scattering techniques and rheological experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The copolymer was synthesized through sequential living anionic polymerization of styrene and isoprene followed by selective saturation of the isoprene block [23]. Because the two polymer species are immiscible, the minority polystyrene forms spherical microdomains within the majority poly(ethylene-alt-propylene).…”
Section: Experimental Systemmentioning
confidence: 99%
“…Furthermore, it was shown that orientation phenomena take place in large amplitude oscillatory shear flow [4]. The works of Sebastian et al [5,6] reveal that the lattice structure of an ordered polystyrene-block-polyisoprene diblock copolymer melt can be broken up in steady shear. This shear-induced disordering is reflected in the rheological quantities.…”
Section: Introductionmentioning
confidence: 99%